Legal Consequences For The Guarantee Agreement Of The Warehouse Receipt Made With The Deed - Dewa Made Ari Widiyatmika (Warmadewa Press, 2018)
In the legislation concerning the Warehouse receipt system in Indonesia, there is no explanation of the form of the agreement to impose security rights on warehouse receipts. As a result, the agreement is made under private a deed. The purpose of this study is to find out related provisions to legal consequences of the agreement to impose security rights on warehouse receipts made with the deed under hand. The research method used in this study is normative juridical method with statute approach. The data of the study were collecting by examining primary legal materials, namely legislation and secondary legal material in the form of doctrines or theories obtained from legal literature and scientific research. Results of the study show that the conditions that must be fulfilled in preparing the agreement to impose the guarantee rights on the Warehouse receipt encompass the validity of the ownership of the Warehouse receipt, the validity of the agreement based on Article 1320 of Indonesian BW. The agreement to impose the guarantee right on the Warehouse receipt is made with an authentic deed, and notification to the registration center or BAPPEBTI. The legal consequence of the agreement to impose the guarantee right on the warehouse receipt made under the deed of hand is that it does not have perfect verification power in the event that one party can still deny the signature in the deed under hand, and another supporting evidence is required in the court to prove the truth of the deed under the hand. It is different from an authentic deed made by a general official who has perfect verification power (volledig) and is binding (blindende).